Dimensions of negative affectivity and age as sources of procrastination in university students in Serbia - Safiye, Teodora; Vukčević, Branimir (Psihološka istraživanja, 2020)
In this study, the aim was to examine whether depression, anxiety, stress, and age were significant predictors of procrastination. The research is based on theoretical concepts and empirical research on procrastination, given by Knaus, Lay, Steele and others. They define procrastination as the intentional postponement of the beginning or completion of a task or job, leaving it for later, despite the knowledge of the negative consequences of such an act. The assumption was that with a higher degree of depression, anxiety and stress, the degree of general procrastination would be higher, and that with a higher age, the degree of procrastination would be lower. The sample consisted of 338 students of both sexes (282 female), average age of 23.53. The following instruments were used: The General Procrastination Questionnaire (GPS: Lay, 1986), Depression, Anxiety, and Stress Scale (DASS-21: Lovibond & Lovibond, 1995), and Questionnaire on sociodemographic data designed for the purposes of this research. Standard multiple regression analysis was used for data analysis. The results show that only depression, in the female subsample, is a significant predictor of procrastination (ß=0.36, p<0.01), which means that in female students depression, including demoralization, experiences of hopelessness and low positive affectivity, strengthens procrastination. The results of the research did not confirm the initial assumption that the older students are, the better they know how to cope with procrastination.